Anisotropic estimates for H(curl)- and H(div)- conforming elements on prisms and applications - Jawtuschenko, Alexis Boris (2015)
We prove anisotropic local interpolation error estimates for two different operators and use this result to estimate the global approximation error for the mixed formulation of the Poisson problem with Dirichlet conditions in a non-convex polyhedraldomain with edge singularities.